Differentiating Hemolysis, Elevated Liver Enzymes, and Low Platelet Count Syndrome and Atypical Hemolytic Uremic Syndrome in the Postpartum Period. Issue 3 (19th July 2021) - Burwick, Richard M.; Moyle, Kimberly; Java, Anuja; Gupta, Megha
Abstract : Supplemental Digital Content is available in the text. Abstract : Pregnancy-associated atypical hemolytic uremic syndrome (aHUS) is a life-threatening thrombotic microangiopathy which may be mistaken for hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome. We sought to identify laboratory parameters that differentiate aHUS and HELLP syndrome in the postpartum period. PubMed was searched from inception to March 2018 to identify cases of aHUS in the postpartum period, while cases of HELLP syndrome were identified from a cohort of deliveries at our institution from January 2015 to December 2018. Postpartum laboratory data were abstracted as either peak values (AST [aspartate transaminase]; creatinine; LDH [lactate dehydrogenase]) or nadir values (hemoglobin; platelet count). Differences were compared using the t test, Wilcoxon Rank Sum, or χ 2 test, and receiver operating characteristic (ROC) curve analyses were performed. We identified 46 cases of aHUS and 45 cases of HELLP syndrome in the postpartum period. Women with HELLP syndrome were older, but rates of nulliparity and cesarean delivery, and gestational age at delivery, were similar between groups. Peak serum creatinine and LDH values after delivery were the most useful to diagnose aHUS with area under the curve 0.996 (95% CI, 0.99–1.0) and 0.91 (95% CI, 0.83–0.98) respectively. Serum creatinine ≥1.9 mg/dL, LDH ≥1832 U/L, or serum creatinine ≥1.9 mg/dL in combination with LDH ≥600 U/L were the optimal thresholds for diagnosing pregnancy-associated aHUS. We conclude that standard laboratory data, most specifically peak serum creatinine and LDH, may be used to differentiate aHUS and HELLP syndrome in the postpartum period.